Pertumbuhan dan Hasil Tanaman Kedelai Pada Pemberian Beberapa Konsentrasi Eko Enzim - Nerty Soverda; Jasminarni Jasminarni; Elly Indra Swari; Pernata Sihombing (Jurnal Media Pertanian, 2023)
Soybean is a food crop that has an important role in increasing national food security. To achieve maximum soybean productivity, plants need adequate nutrition, namely through fertilization. The limited availability of fertilizer greatly affects farming activities. Therefore, the use of organic fertilizer is one solution to this problem.This research was carried out at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, UNJA Mendalo Campus, Mendalo Indah Village, Jambi Luar Kota District, Muaro Jambi Regency in approximately 4 months starting from 10 January to 30 April 2023. This research used a Randomized Block Design (RAK) one factor is the provision of Eco Enzyme concentration at 5 levels, namely: p0 = Eco enzyme 0 mL L-1, p1 = Eco enzyme 10 mL L-1, p2 = Eco enzyme 15 mL L-1, p3 = Eco enzyme 20 mL L-1, p4 = Eco enzyme 25 mL L-1.The results of this study showed that administration with several concentrations of Eco Enzyme gave different responses to plant height, number of pods per plant, number of pods containing plants, number of primary branches, weight of 100 seeds and yield per hectare and had no significant effect on the flowering rate of the plants. Giving Eco Enzyme with a concentration of 20 mL L-1 water is the best concentration.